IMPLEMENTASI PERDA NO. 09 TAHUN 2009 TENTANG USAHA PERKEBUNAN DI KABUPATEN KUANTAN SINGINGI (Studi Tentang Perizinan Surat Tanda Daftar Usaha Budidaya Perkebunan (STD-B)) - Wahyudi, Egi Fitrah; Yuliani, Febri (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2017)
Plantation is one of the strategic sub-sector that is economically, takes an important role in regional development of Kuantan Singingi Regency, considering that most of the people engaged in this subsector. The high of plantation business activity which is not have license in Kuantan Singingi Regency is happen continuously and tend increasingly prevalent in the society to fulfil the needs of life, so sometimes lead to social conflicts, which makes policy for the Plantation Business more seriously implemented. The problem in this research is how the implementation of the Regional Regulation No. 9 2009 on Plantation Business in Kuantan Singingi (Study on the Licensing Plantation Cultivate Bussiness Registration Card (STD-B)) and what are the factors that obstruct the implementation of the policy. As for the purpose of this study is to determine and analyze the implementation of the Regional Regulation No. 9 2009 on Plantation Business in Kuantan Singingi (Study on the Licensing Plantation Cultivate Bussiness Registration Card (STD-B)) and to determine and analyze the implementation of the policy.The concept of the theory that that the writer uses is the policy and the policy implementation. And the theory used is the theory of Grindle with two variables: the contents of the policy and implementation environment. This study uses qualitative research methods with a descriptive data assessment. In collecting the data, the writer uses interview, observation and documentation. Using the key informants as the source of information.The results of this study showed that the implementation of the Regional Regulation No. 9 2009 on Plantation Business in Kuantan Singingi (Study on the Licensing Plantation Cultivate Bussiness Registration Card (STD-B)) has not run optimally. Thr factors which is obstruct the implementation of the policy of the Plantation Business are human resources from the actor of policy, the less of socialization to the target groups and the less of compliance and responsiveness of the society in the registration of the license of Plantation Business STD-B. Keywords: Policy, Implementation of policy, License Plantation Business STD-B